PENGARUH PELAYANAN PENDAFTARAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RSKIA PKU MUHAMMADIYAH KOTAGEDE YOGYAKARTA: PENGARUH PELAYANAN PENDAFTARAN TERHADAP KEPUASAN PASIEN RAWAT JALAN DI RSKIA PKU MUHAMMADIYAH KOTAGEDE YOGYAKARTA - Suliantoro, Suliantoro; Fatchurahim, Dedy (LPPM Akademi Manajemen Administrasi Yogyakarta, 2022)
The purpose of this study was to determine the effect of registration services on outpatient satisfaction at RSKIA PKU Muhammadiyah Kotagede Yogyakarta. The population taken was outpatients at RSKIA PKU Muhammadiyah Kotagede Yogyakarta which amounted to 50 as a sample. Data collection was carried out by distributing questionnaires to respondents. Collection technique using SPSS.17. Based on the results of the study, it was stated that the service variable had a positive and significant effect on employee performance had a significant value of 0.007 < 0.05 and the t test with a calculated t value of 3.097 > t table 1.677.